Assessing change in psychoanalytic psychotherapy of children and adolescents : today's challenge - Tsiantis, J. (John); Trowell, Judith (EFPP clinical monograph series., 2010)
This book draws together work from across Europe by leading clinical researchers who have been looking into the effectiveness of psychoanalytic interventions. They are mostly time limited, brief, non-intensive ways of working so are applicable in many settings and can therefore be generalised to other clinical teams. The populations worked with are diverse and often present mainstream services with refractory clinical problems, so an applied psychoanalytic approach is well worth trying given the evidence presented in this volume. There is in addition an excellent theoretical chapter on the issu.